2010
DOI: 10.2514/1.40592
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Modeling of Two-Body Interaction in Supersonic Flow

Abstract: Atmospheric and space launch stage separation depends on the aerodynamic interference between separating bodies. Quick means of estimating and controlling repulsion or attraction lift associated with this interaction are an important enabling technology to achieve the best compromise between launch separation rocket motor weight and safe staging. Asymptotic methods, scattering, and slender-body theories are used to obtain systematic approximation schemes that advantageously couple with computational methods. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In addition to the research which discusses the overall interference loads, it is important to understand the detailed underlying flow physics. Of particular interest are the shock-body interactions which have been studied previously for a number of configurations 9,10,13,15 . Brosh 16 and Hung 2 investigated a wedge-generated shock impinging on a cylinder at M ∞ =3 and showed that the shock footprint, in terms of local pressure rise, decreased as the shock diffracted around the body.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the research which discusses the overall interference loads, it is important to understand the detailed underlying flow physics. Of particular interest are the shock-body interactions which have been studied previously for a number of configurations 9,10,13,15 . Brosh 16 and Hung 2 investigated a wedge-generated shock impinging on a cylinder at M ∞ =3 and showed that the shock footprint, in terms of local pressure rise, decreased as the shock diffracted around the body.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Volkov 9 investigated the effect of lateral separation between two axially aligned slender bodies and found reasonably good agreement between the measured and calculated loads. Finally, both Malmuth 10 and Fedorov 15 have reported theoretical approaches to the calculation of overall loads on two slender bodies in close proximity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to studies which report the overall interference loads, it is important to understand the detailed underlying flow physics. Of particular interest are the shock-body interactions which have been studied previously for a number of configurations [7,8,[11][12][13][14][15]. Brosh et al [14] and Hung [2] investigated a wedge-generated shock impinging on a cylinder at M ∞ =3 which showed that the shock footprint, in terms of local pressure rise, decreased as the shock diffracted around the body.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Volkov and Derunov [7] investigated the effect of lateral separation between two axially aligned slender bodies and found reasonably good agreement between the measured and predicted loads. Finally, both Malmuth and Shalaev [8] and Fedarov et al [13] have reported theoretical approaches to the prediction of overall loads on two slender bodies in close proximity.…”
Section: Introductionmentioning
confidence: 99%